Rancangan Perbaikan Tata Letak Tool Storage Dengan Metode CBS Pada PT. IPP - Suryobuwono, Abdullah Ade; Noviansyah, Denny; Puspita, Sesaria Maedhiani Rachma; Herlangga, Harya (Institut Transportasi dan Logistik Trisakti, 2023)
This research aims to determine, analyze and improve the layout of the storage warehouse at PT. IPP using the Class Based Storage Method. Materials that move quickly or are fast moving are stored close to the loading/unloading door to minimize material transportation distance. Company PT. IPP operates in the field of maintenance, repair and overhaul (MRO) services. The cause of the inefficient layout of goods in the warehouse is because there are no employees dedicated to the warehouse section so that the placement of goods becomes irregular. Based on the research, the results of the ABC classification in this study obtained three groups, namely where goods with a faster frequency of moving in and out were classified into group A, then goods which moved quickly but were not too close to the door were clarified into group B and items whose movements slow and far from the exit are classified as group C, clarification according to the frequency of material handling movement distance. After making a proposed warehouse layout, the results were able to minimize the distance moved during material handling in the initial warehouse layout of 7,033/month to a smaller value, namely 3,460/month. So it can be concluded that the Class Based Storage Method can be applied in companies so that the warehouse layout becomes more efficient.